Nanopartículas magnéticas: efeitos da forma e tamanho finito de amostras cristalinas e análise da influência do porta-amostras nas medidas das propriedades magnéticas de sistemas de partículas interagentes - Lima, Ana Tereza de Abreu (2022)
In this work, numerical procedures were developed that allow the investigation of the effects of shape and volume on the magnetic properties of nanostructured antiferromagnética particles. The techniques used make it possible to calculate the remanence, coercivity, saturation magnetization and normal modes of vibration of one particle and relate these properties to its volume, shape and magnetic configurations. Nanostructured particles were described through their crystal lattices and magnetic energy. The magnetic characteristics, exchange constants and anisotropy fields, of Manganese Difluoride (MnF2) and Nickel Oxide (NiO) were used to determine the numerical results and it was observed that the volume and shape affect the magnetic properties of these materials. The presence of the surface breaks the symmetry of the magnetic network of the nanoparticles, producing a reorganization of the magnetic moments close to this region. On the other hand, considering that the measurements of magnetic properties are carried out on a set of particles, using containers to accommodate the samples, and that the shape of these sample holders produces anisotropies that affect the measured properties, an investigation was carried out seeking to understand how the Container shape influences the measurements of magnetic properties of these materials, through the calculation of magnetization and normal modes of vibration. Cylindrical and triangular-based containers were investigated, containing a powder consisting of magnetic and non-magnetic particles in different concentrations. The analysis of these particle agglomerates showed that their static and dynamic behavior are influenced by the shape of the container that contains them and that this effect depends on the concentration of magnetic material.